ANALISIS FAKTOR PERILAKU ANAK SD KELAS 4 – 5 DALAM PERAWATAN KESEHATAN GIGI TERHADAP KEJADIAN KARIES PADA SISWA SD SWASTA PARULIAN 2 KOTA MEDAN TAHUN 2022 - JULIKE, KATARINA; ERWINSYAH, ERWINSYAH; Linggom, Tampak; Iqbal, Muhammad (Deli Medical and Health Science Journal, 2024)
Dental caries is a first-rate problem in children's oral hollow space to date. school-age youngsters, especially primary faculty youngsters, are a set this is liable to dental and oral sicknesses because generally those kids still have behaviors or conduct that don't aid dental health.The cause of this reasearch to analyze the behavioral factors of basic faculty youngsters in grades IV–Vin dental health care for the occurrence of caries in students of private standard faculty Parulian 2 Medan city in 2022.This form of research is an observational analytic survey look at with a Case control examine design, to evaluate the case institution and the control institution based totally on their exposure reputation.The population in this look at had been all 38 college students in grades IV-V at Parulian 2 personal standard school in 2022 who had dental caries on their permanent tooth. The effects confirmed that there was a massive relationship between age (p=0.001), gender (p=0.022), socioeconomic (p=0.022), and the incidence of dental caries. there is a extensive relationship among knowledge (p=0.028) and attitude (p=0.010) with the occurrence of dental caries. there's a big dating among how to brush your teeth (p=zero.001), frequency of brushing your enamel (p=0.039), time of brushing your enamel (p=zero.021), frequency of going to the dentist (p=zero.000), and the occurrence of dental caries (p=0.039 ), teeth brushing gear (p=zero.031) with the occurrence of dental caries.Multivariate outcomes showed that the maximum dominant variable influencing the threat of dental caries turned into the variable frequency of going to the dentist with Exp B = 14.609 (ninety five% CI: 2.824-seventy five.592). it is for the government and software holders on the puskesmas, specifically UKGS, to in addition growth the provision of education approximately dental caries to faculties, as well as carry out ongoing dental care for simple college youngsters.